Bioequivalence and safety assessment of sorafenib tosylate tablets in healthy Chinese subjects under fasting conditions - Wang, Zhaoyu; Peng, Hong; Zhang, Yun; Chen, Xijing; A, Jiye (Frontiers in Pharmacology, 2025)
ObjectiveThis study aimed to assess the bioequivalence and safety of two formulations of sorafenib in healthy Chinese subjects under fasting conditions.MethodsA single-center, randomized, open, single-dose, two-formulation, four-period, crossover study was performed in 36 healthy Chinese subjects under fasting conditions. Blood samples were collected within 120 h after administration. The plasma concentrations of sorafenib were analyzed by a validated UPLC-MS/MS method, and pharmacokinetic parameters were analyzed using a non-compartmental method. Safety was assessed on the basis of the occurrence of adverse events and laboratory findings throughout the study period.ResultsThe GMR point estimators of Cmax, AUC0-t, and AUC0-∞ for the two formulations were 88.97%, 81.67%, and 83.66%, respectively, which were within the bioequivalence criterion range of 80%–125%. The upper limits of the one-sided 95% confidence intervals of Cmax, AUC0-t, and AUC0-∞ after logarithmic transformation were −0.05, −0.04 and −0.03, respectively, which were less than 0. The difference in Tmax between these two formulations was not statistically significant according to the Wilcoxon signed-rank test (P = 0.3650 > 0.05). Therefore, the bioequivalence between the two formulations was established under fasting conditions. All adverse events were mild and transient.ConclusionThe T formulation was bioequivalent and showed a similar safety profile to the R formulation Nexavar® (Bayer AG) in healthy Chinese subjects under fasting conditions.Clinical trial registrationhttp://www.chinadrugtrials.org.cn/index.html, Identifier CTR20233578.